1998
DOI: 10.1302/0301-620x.80b1.7987
|View full text |Cite
|
Sign up to set email alerts
|

The extended lateral approach to the hindfoot: Anatomical basis and surgical implications

Abstract: We have recently described an extended lateral approach to the hindfoot for the operative treatment of displaced intra-articular fractures of the calcaneum. It has the advantage of avoiding damage to the sural nerve and preserving blood supply to allow prompt healing. We dissected 15 formalin-preserved cadavers, taking photographs to show the structures of the posterolateral aspect of the hindfoot and ankle. We describe a superficial and a deep triangle: the deep triangle contains a constant posterior peroneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 0 publications
3
45
0
3
Order By: Relevance
“…This considerable rate of wound infections is more likely the result of our type of surgical approach. As we recently started performing calcaneal surgery more often by an even more extended lateral approach according to Freeman et al [28] and (in less complex fractures) via the sinus tarsi approach [29,30], the severe wound complication rates appear to have decreased. In the latter type of approach a wound complication rate of 29 % in the ELA versus 6 % in the less invasive sinus tarsi approach was described [31].…”
Section: Discussionmentioning
confidence: 99%
“…This considerable rate of wound infections is more likely the result of our type of surgical approach. As we recently started performing calcaneal surgery more often by an even more extended lateral approach according to Freeman et al [28] and (in less complex fractures) via the sinus tarsi approach [29,30], the severe wound complication rates appear to have decreased. In the latter type of approach a wound complication rate of 29 % in the ELA versus 6 % in the less invasive sinus tarsi approach was described [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, its main drawback is the high wound complication rate [1][2][3][4][5]. Various anatomic studies concluded that injury of the lateral calcaneal artery (LCA) at the site of the vertical incision is responsible for ischemia and necrosis of the lateral calcaneal flap [14][15][16]. In an attempt to reduce the wound complication rate, numerous minimally invasive and percutanous methods were developed [6][7][8][9][10][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…All of the lower limbs were amputated at the level of the tibial diaphysis. An extended lateral approach was performed on all specimens [16]. The dissected fasciocutaneous flap was then removed to expose the calcaneum.…”
Section: Methodsmentioning
confidence: 99%